STRATEGI ADAPTASI PETANI DI LAHAN MARGINAL (STUDI KASUS PETANI UBI KAYU DI DESA JAYA MAKMUR KECAMATAN BINONGKO KABUPATEN WAKATOBI) - Harsandi, Lisa; Arimbawa, Putu; Mardin, Mardin (Fakultas Pertanian Universitas Halu Oleo, 2023)
This study aims to assess the resources available to farmers and their adaptation strategies for cassava farming on marginal land in Jaya Makmur Village, Binongko District. The study population comprises 193 cassava farmers in Jaya Makmur Village. The informants were selected using the snowball sampling technique based on specific criteria, resulting in a total of 8 informants who met the criteria. The study employed observation, interviews, and documentation methods with research instruments in the form of interview guides to collect data. The data analysis method used was descriptive qualitative analysis, which involved three stages: data reduction, data presentation, and conclusion drawing. The study suggests that cassava farmers on marginal land in Jaya Makmur Village face various challenges, including limited resources, economic factors, climate variability, soil quality, and social factors. To address these issues, farmers employ different adaptation strategies, such as active, passive, and network strategies.